2013
DOI: 10.2478/s13382-013-0081-7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of environmental domain of quality of life in economically active population living in Silesian agglomeration, Poland

Abstract: Objectives: The aim of this paper is to identify the factors that determine the environmental domain of quality of life in economically active adults living in the industrial agglomeration in Poland. Materials and Methods: During the crosssectional epidemiological study conducted among the economically active population aged 45-60, we used a short version of the WHOQOL-BREF questionnaire. Respondents were recruited randomly from selected factories located in the Silesian Agglomeration. The statistical analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…N=300. *p value less than 0.05 is considered as significant best [16]. Studies have shown that psychological factors and sociodemographic characteristics such as marital status and others had an impact on QOL of elderly population [9].…”
Section: Discussionmentioning
confidence: 99%
“…N=300. *p value less than 0.05 is considered as significant best [16]. Studies have shown that psychological factors and sociodemographic characteristics such as marital status and others had an impact on QOL of elderly population [9].…”
Section: Discussionmentioning
confidence: 99%
“…The results were analyzed in three stages, taking into account (1) a description of the intensity levels of results in the measured domains of life of the respondents, (2) an assessment of the relationship between quality of life and resource gains and losses as well as the frequency of using coping strategies, and (3) a selection of variables most accurately predicting the level of quality of life in the COVID-19 context. 19 12 An analysis of the four main domains measured in the WHOQOL-BREF regarding the midpoint for the estimation scale of the response format indicates that the studied group has relatively high and, at the same time, very similar results in all the four domains of quality of life [22]. A juxtaposition of responses with the midpoint of the estimation scale suggests that respondents also have average resource gains and low resource losses.…”
Section: Resultsmentioning
confidence: 98%
“…Quality of life. Quality of life was measured with the WHO Quality of Life-BREF (WHOQOL-BREF), an abbreviated generic Quality of Life Scale developed through the World Health Organization [21,22]. It is an international cross-culturally comparable quality of life assessment instrument developed with 15 international field centers simultaneously.…”
Section: Gain and Loss Of Resources The Polish Version Of The Consermentioning
confidence: 99%
“…It is worth noting that the final size of the study group (N = 5136) complies with the criteria required for the cross-sectional study. The general public interest in the impact of living environment on the health and quality of life in our region of study [33] makes one's own observation an important voice as far as public health is concerned. Obtained results may be precious for public health experts and decisionmakers in the range of future studies and planned activities in the field of environmental health.…”
Section: Discussionmentioning
confidence: 99%